HTLV-1 associated myelopathy in Canada. - Power, C; Weinshenker, BG; Dekaban, G; Ebers, G; Francis, G; Rice, G (1989)
We report the clinical and laboratory findings of six Canadian patients with progressive myelopathy associated with HTLV-1 infection. The diagnosis was suspected on clinical grounds and supported by serological studies and positive gene amplification. Only five had emigrated from an area endemic for HTLV-1 infection. Tropical spastic paraparesis should be considered in all patients with myelopathy, even those without standard serological markers of HTLV-1 infection. The pathogenesis of this condition and the serological and molecular biological means by which this diagnosis can be made are reviewed.